Estimating the probability of accidents on building scaffoldings. (August 2022) - Nowobilski, Tomasz; Hoła, Bożena
Highlights: Empirical determination of the number of building scaffoldings in use in representative areas of the examined region. Development of mathematical models that enable the number of scaffoldings on the basis of selected socio-economic indicators. Prediction of the number of scaffoldings that are in use in the region covered by the research. For every 10, 000 scaffoldings in use, two accidents may occur, which is equivalent to a minimum of two injured people. Abstract: The aim of the research that was conducted and presented in the article was to estimate the posterior probability of occupational accidents involving scaffoldings. The research was conducted in five regions of Poland. The authors' original research methodology was developed, which used: the results of empirical research involving the counting of scaffoldings used in selected representative areas of the studied regions; information concerning the number of occupational accidents involving scaffoldings, which was obtained from the District Inspectorates of the National Labour Inspectorate; and also data from publications of the Central Statistical Office concerning socio-economic indicators characterizing the surveyed regions. The main element of the developed methodology involved multivariate linear regression models, which were used to predict the number of scaffoldings in each studied region. The quantitative analysis of the identified accidents, in conjunction with the estimated population of scaffoldings, allowed for the estimation of the incidence rate of the occurrence of an accident involving scaffolding with regards to all the used construction scaffoldings. In this way, the incidence rates of accidents involving scaffoldings W, which indicate how many accidents occur for every 10, 000 used scaffoldings, were obtained. The average value of the W index for the analyzed period of time and the five analyzed regions of the country amounted to 1.89. This means that for every 10, 000 used scaffoldings, approximately two accidents may have occurred, which is equivalent to a minimum of two injured people. The obtained results of research and analyses show the scale of the phenomenon of accidentality that is related to the use of scaffolding in the studied regions. They constitute the basis for comparing regions in terms of occupational safety on scaffolding. They can also be used to predict the probability of an accident in the future. The acquired knowledge can be used in the process of occupational safety management on scaffoldings. Commonly known mathematical tools, such as linear regression and neural networks, were used to solve the given task. All calculations were made using Statistica software.